Gerakan adaptasi pangan lokal “pangan bijak nusantara” mendukung sistem pangan berkelanjutan Indonesia - Marthalia, Lusye; Frimawaty, Evi (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Food is an important issue in meeting human needs and life, which currently faces many challenges. Background: This paper aims to present the role of the